The Effects of Health Insurance within Families : Experimental Evidence from Nicaragua - Fitzpatrick, Anne; Thornton, Rebecca (Published by Oxford University Press on behalf of the World Bank, 2021)
This paper measures the causal effects of parent enrollment into voluntary health insurance on healthcare utilization among insured and uninsured children in Nicaragua. The study utilizes a randomized trial and age-eligibility cutoff in which insurance subsidies were randomly allocated to parents that covered their dependent children under 12; children age 12 and older were not eligible for coverage. Among eligible children, the insurance increased utilization at covered providers by 0.56 visits and increased overall utilization by 1.3 visits. Ineligible children with insured parents experienced 1.7 fewer healthcare visits driven by parent, not sibling, enrollment. The results suggest complementarities across healthcare provider type and provide evidence that households reallocate resources across all members in response to changes in healthcare prices for some.